Needs Analysis for The Development of a Manual in Palliative Care forMalaysia: AnIslamic Psychospiritual Approach - Nor Azah binti Abdul Aziz (Tanjung Malim, 2024)
Needs Analysis for The Development of a Manual in Palliative Care forMalaysia: AnIslamic Psychospiritual Approach by Nor Azah binti Abdul Aziz